Posada's Mexico (Library of Congress [etc.], 1979)
Catalog of an exhibition held at Library of Congress, Washington, D.C., Nov. 1, 1979-Jan. 1, 1980, the Amon Carter Museum of Westen Art, Fort Worth, Tex., Jan. 25-Mar. 9, 1980, and the Colorado Springs Fine Arts Center, Colorado Springs, Colo., Apr. 26-June 1, 1980. - Bibl., index.